التعامل بتقنية الإعتماد المستندي في البنوك الإسلامية - دهانة, بشير (University of Eloued جامعة الوادي, 2020)
هدفنا من خلال هذه الدراسة التعرف على آلية استخدام تقنية الإعتماد المستندي لدى البنوك الإسلامية، يكون هذا من خلال التعرض بالوصف والتحليل لأنظمة بنك الجزائر، على اعتبار أن هذه التقنية أضحت مهمة في تمويل التجارة الخارجية بالنسبة للمتعاملين الاقتصاديين والبنوك. وقد خلصت الدراسة أن تقنية الإعتماد المستندي تلائم البنوك الإسلامية نظريا بينما واقعيا هناك إشكالات تعاني منها البنوك الإسلامية في تمويل التجارة الخارجية، وقدرتها على خلق موارد وتمويل المشروعات للعملاء. Abstract: The aim of this study is to identify the mechanism of using documentary credit in the Islamic banks, It is through describing and analyzing the systems of the Bank of Algeria, given that this technique has become important in financing foreign trade for economic dealers and banks. The study concluded that the documentary credit technique fits the Islamic banks in theory, while in reality there are problems that Islamic banks suffer from in financing foreign trade, and their ability to create resources and finance projects for clients. ا
Dealing with Documentary Credit technique in Islamic Banks
مقال
Keywords: الإعتماد المستندي ; البنوك الإسلامية ; التجارة الخارجية ; المستورد ; المصدر; Documentary Credit ; Islamic Banks ; Foreign Trade ; Importer ; Exporter